Concentrado proteico de linhaça como substituto do farelo de soja na dieta de jundiás (Rhamdia Quelen) - Cargnin, Gregorio (2023)
This work aimed to evaluate the effects of replacing soybean meal with flaxseed protein concentrate (FLC) in silver catfish (Rhamdia quelen) diets on metabolic parameters, antioxidants and pro-oxidants, digestive indices, body composition, nutrient deposition and body performance and growth. The CPL was obtained from the sequence of three physical processes, which involved demucilage, separation of the bark and endosperm and oil extraction. Being subjected to analysis of chemical composition, physicochemical properties and electrophoresis. Subsequently, a biological assay was carried out testing CP replacement levels (0, 15, 30, 45 and 60%) of soybean meal by CPL in catfish diets (3.52 ± 0.10g). 360 animals were distributed in 20 tanks (18 animals) and fed for 27 days with the experimental diets. At the end of the experimental period, they were submitted to biometrics to collect data and tissues for further analysis. Plasma and hepatic metabolites, pro and anti-oxidant enzymes, digestive enzymes, body composition and nutrient deposition, body performance and growth were evaluated. The experimental design was completely randomized, with five treatments and four repetitions. The data were submitted to the normality test, analysis of variance and the averages compared by Tukey's test (P<0.05). The results show that replacing soybean meal with CPL impacts fish metabolism, increasing total protein, plasma cholesterol, hepatic free amino acids (45% CPL) and hepatic ammonia (15% CPL). The activity of TBARS, protein carbonyl, ROS and ACAP in the liver and gills were higher in those fed with the control diet. The activity of GST (liver and gills) increased according to the increase in CPL in the diets. Trypsin was higher in those fed the control diets compared to 30% and 45% CPL. Final weight, biomass, TCE and consumption were higher in fish that received a diet with 15% CPL. Regarding body composition, differences were observed only for crude protein, which was higher in fish that consumed diets with 15 and 30% CPL. As for nutrient deposition, the fish that consumed the diet with 15% of CPL had greater deposition of protein and fat, and for the latter, there was also greater deposition in fish fed with 30 and 45% of CPL. The other evaluated parameters were not significantly influenced by the CPL levels tested. When CPL was included as a substitute for soybean meal in catfish diets, the product showed promising results from a metabolic and antioxidant point of view, indicating its viability for use in fish feed.